POLITIK HUKUM PELEMBAGAAN KOMISI-KOMISI NEGARA DALAM SISTEM KETATANEGARAAN INDONESIA - Alamsyah, Bunyamin; Huda, Uu Nurul (Jurnal Hukum dan Peradilan, 2013)
During the 32 years of the New Order government certainly has its advantages and disadvantages, in terms of the development of infrastructure and supra-structure growing rapidly, but the journey has decreased function of government and its role even stagnant. Therefore, there was the Reform of 1998 in a variety of fields. In reply funsgi decline and the role of government under the Constitution of 1945, there was an opinion with the formation of a new organization outside the government. Gagsan ideas are realized with the establishment of committees that do not require the State budget a little, sometimes a clash of authority between committees also with government agencies. Committees should not be separated from the politics of law. Keywords: Institutionalization of Political Law, Commissions of the State, State Administration System